Impaired Performance of the Q175 Mouse Model of Huntington’s Disease in the Touch Screen Paired Associates Learning Task - Piiponniemi, Tuukka O.; Parkkari, Teija; Heikkinen, Taneli; Puoliväli, Jukka; Park, Larry C.; Cachope, Roger; Kopanitsa, Maksym V. (Frontiers in Behavioral Neuroscience, 2018)
Cognitive disturbances often predate characteristic motor dysfunction in individuals with Huntington’s disease (HD) and place an increasing burden on the HD patients and caregivers with the progression of the disorder. Therefore, application of maximally translational cognitive tests to animal models of HD is imperative for the development of treatments that could alleviate cognitive decline in human patients. Here, we examined the performance of the Q175 mouse knock-in model of HD in the touch screen version of the paired associates learning (PAL) task. We found that 10–11-month-old heterozygous Q175 mice had severely attenuated learning curve in the PAL task, which was conceptually similar to previously documented impaired performance of individuals with HD in the PAL task of the Cambridge Neuropsychological Test Automated Battery. Besides high rate of errors in PAL task, Q175 mice exhibited considerably lower responding rate than age-matched wild-type animals. Our examination of effortful operant responding during fixed ratio and progressive ratio reinforcement schedules in a separate cohort of similar age confirmed slower and unselective performance of mutant animals observed during PAL task but suggested that motivation to work for nutritional reward in the touch screen setting was similar in Q175 and wild-type mice. We also demonstrated that pronounced sensorimotor disturbances in Q175 mice can be detected at early touch screen testing stages, (e.g., during “Punish Incorrect” phase of operant pretraining), so we propose that shorter test routines may be utilised for more expedient studies of treatments aimed at the rescue of HD-related phenotype.